Transmission measurement at the Bernina branch of the Aramis Beamline of SwissFEL. (24th October 2019) - Juranic, Pavle; Tiedtke, Kai; Owada, Shigeki; Tanaka, Takahiro; Jastrow, Ulf; Sorokin, Andrey; Patthey, Luc; Mankowsky, Roman; Degenhardt, Markus; Arbelo, Yunieski; Arrell, Christopher; Smedley, John; et al.
Abstract : The transmission of the optical components of the Bernina branch of the Aramis beamline at SwissFEL has been measured with an X‐ray gas monitor from DESY and compared with a PSI gas detector upstream of the optical components. The transmission efficiencies of the mirrors and the various other in‐beam components were evaluated and compared with theoretical calculations. Abstract : The transmission of the optical components of the Bernina branch of the Aramis beamline at SwissFEL has been measured with an X‐ray gas monitor from DESY and compared with a PSI gas detector upstream of the optical components. The transmission efficiencies of the Mo, Si and SiC mirror coatings of the Aramis beamline and the various other in‐beam components were evaluated and compared with theoretical calculations, showing an agreement of 6% or better in all cases. The experiment has also shown the efficacy of the high‐harmonic rejection mirrors at the Bernina branch of the Aramis beamline at SwissFEL, and characterized the transmission efficiency of the on‐line spectrometer in the Aramis beamline. The theoretical transmission of the mirror coatings match the experimental data to within 7%. The accuracy of these measurements was checked against a radiative bolometer from a Japanese collaboration and found to agree to a level of 4% or better. Further comparisons with a diamond detector from a US‐based inter‐institute collaboration demonstrated a good agreement for the attenuator settings of the beamline.